Playing the Devil's Advocate: The Causal Effect of Risk Management on Loan Quality - Berg, Tobias (Review of Financial Studies, 2015)
This paper studies the dual role of risk managers and loan officers in a bank's organizational structure. Using 75,000 retail mortgage applications, I analyze the effect of risk-management involvement on loan default rates. The bank requires risk-management approval for loans that are considered risky based on hard information, using a sharp threshold that changes during the sample period. Using a regression discontinuity design and a difference-indifferences estimator, I am able to show that risk-management involvement reduces loan default rates by more than 50%. My findings suggest that a two-agent model can help to facilitate efficient screening decisions.